Challenge and Creativity: Using .NET Gadgeteer in Schools (Best Paper Award) - Schwiderski-Grosche, Scarlet; Sentance, Sue (Proceedings of 7th Workshop on Primary and Secondary Computing Education (WIPSCE '12), 2012)
This paper reports on a study carried out in secondary schools in the UK with students learning to use .NET Gadgeteer, a rapid prototyping platform for building small electronic devices. A case study methodology has been used. Some of the students involved in this four-month-long project had some prior background in computer programming whereas for others this was completely new. The teaching materials provided a two-phase model of learning: an instruction phase followed by a creative phase, the latter utilising a bricolage approach to learning programming. The aim of the pilot was to generate an interest in building devices and stimulate creativity. The research found that the tangible nature of the .NET Gadgeteer modules helped to engage the students in becoming creative, and that students valued challenges with which they were not usually presented within the curriculum.
Best Paper Award